2016
DOI: 10.3402/gha.v9.29336
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs, perceptions and health-seeking behaviours in relation to cervical cancer: a qualitative study among women in Uganda following completion of an HPV vaccination campaign

Abstract: BackgroundCervical cancer remains a leading cause of morbidity and mortality in Uganda. Despite earlier information campaigns to introduce human papilloma virus (HPV) vaccination, which also targeted cervical cancer, misinterpretation and misunderstanding of the subject remain high. Women in Uganda present with cervical cancer at an advanced stage due to poor health-seeking behaviours, with an associated high mortality rate. This project explored beliefs, attitudes, perceptions, and health-seeking behaviours i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 37 publications
5
51
0
2
Order By: Relevance
“…The prior knowledge literacy level was low among women in Mayuge. This result equally compares well with those by Hasahya et al [13], which found that cervical cancer and other cancers are not well understood, especially in rural Ugandan communities. For instance, there are various beliefs and misperceptions among Ugandan women on cervical cancer: some believe it is an incurable disease, a disease from men, a disease whose cause is unknown and in HPV vaccination as a form of family planning.…”
Section: The Level Of Functional Cervical Cancer Literacysupporting
confidence: 89%
See 2 more Smart Citations
“…The prior knowledge literacy level was low among women in Mayuge. This result equally compares well with those by Hasahya et al [13], which found that cervical cancer and other cancers are not well understood, especially in rural Ugandan communities. For instance, there are various beliefs and misperceptions among Ugandan women on cervical cancer: some believe it is an incurable disease, a disease from men, a disease whose cause is unknown and in HPV vaccination as a form of family planning.…”
Section: The Level Of Functional Cervical Cancer Literacysupporting
confidence: 89%
“…In subjective contexts, the perceived prevalence of a disease risk is a potential motivator of health promoting behaviour that can facilitate better utilisation of cancer prevention, detection and control services [37,38]. Hasahya et al [13] found that cervical cancer and other cancers are not well understood, especially in rural Ugandan communities. Some believe it is an incurable disease, a disease from men, a disease caused by family planning, or that the cause is unknown.…”
Section: Factors That Are Known To Influence Hl Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Respecto a las barreras relacionadas con las características del examen, los resultados reportados concuerdan con investigaciones previas donde se señala la vergüenza que genera el examen 14,16,[20][21][22] y el miedo que les provoca el diagnostico de cáncer 4,6,16,23 . En relación a esto último, se ha descrito que hay mujeres que prefieren "no saber de enfermedades que no tienen tratamiento y que pueden llevar a la muerte" 19,22 .…”
Section: Discussionunclassified
“…The persistent infection of high-risk human papillomavirus is associated with a high incidence of cervical cancer (2,3). According to histological phenotypes, cervical cancer is divided into two types: Squamous cell carcinoma (SCC; ~80%) and adenocarcinoma (~5-20%) (4). SCC primarily originates from cervical intraepithelial neoplasia (CIN), but adenocarcinoma results from intraepithelial adenocarcinoma and glandular dysplasia (5,6).…”
Section: Introductionmentioning
confidence: 99%